2015
DOI: 10.1111/cyt.12232
|View full text |Cite
|
Sign up to set email alerts
|

Salivary gland FNA cytology: role as a triage tool and an approach to pitfalls in cytomorphology

Abstract: Salivary gland FNA is crucial in the distinction of non-neoplastic from neoplastic lesions, emphasizing the fact that FNA is an excellent triage tool for surgery. Salivary gland FNA has a high sensitivity and specificity. However, it is important to interpret the cytological diagnoses in the light of clinical findings and imaging. Diagnostic pitfalls are seen in a minority of cases and could potentially be overcome with the help of recently described diagnostic and prognostic markers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
62
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(64 citation statements)
references
References 21 publications
2
62
0
Order By: Relevance
“…The commonest malignant neoplasm was mucoepidermoid carcinoma, as seen in other studies [5,14,16]. Histological follow-up was available only in 21%, similar to a study from the UK by Mairembam et al [17] on 920 aspirates. The 190 cases which had histological follow-up were further analysed.…”
Section: Discussionsupporting
confidence: 72%
“…The commonest malignant neoplasm was mucoepidermoid carcinoma, as seen in other studies [5,14,16]. Histological follow-up was available only in 21%, similar to a study from the UK by Mairembam et al [17] on 920 aspirates. The 190 cases which had histological follow-up were further analysed.…”
Section: Discussionsupporting
confidence: 72%
“…1,15 CAexPA may occasionally represent a challenge in that only the precursor PA component may be sampled and therefore classified as a benign neoplasm. 1,15 CAexPA may occasionally represent a challenge in that only the precursor PA component may be sampled and therefore classified as a benign neoplasm.…”
Section: B a S A L O I D N E O P L A S M Smentioning
confidence: 99%
“…1,2 Despite this very good performance of salivary gland FNA there are limitations and these are mainly related to the inability to provide specific diagnosis in some cases. Multiple studies have shown high sensitivity, specificity and accuracy in the differentiation of benign versus malignant tumors (sensitivity 80-89% and specificity 97% for malignancy).…”
Section: Introductionmentioning
confidence: 99%
“…In the majority of cases, the salivary gland lesions are easily accessible for FNA, either superficially by palpation or by USG. The technique is minimally invasive and well tolerated by patients without significant complications, and is a cost‐effective diagnostic tool with a high sensitivity and specificity of approximately 54% to 98% and 88% to 98%, respectively . FNA plays a key role in guiding clinical management and provides useful information such as distinguishing between a neoplastic and a non‐neoplastic lesion, ascertaining whether a lesion is benign or malignant, and, last, providing prognostic information and a sample for ancillary testing such as molecular studies …”
Section: Introductionmentioning
confidence: 99%